Agricultural Risk Management in the European Union: A Proposal to Facilitate Precautionary Savings. (21st August 2019) - van Asseldonk, Marcel; Jongeneel, Roel; van Kooten, G. Cornelis; Cordier, Jean
Summary: Through a series of reforms, the European Union (EU) replaced most of its trade distorting price support programmes with safety net provisions and direct payments decoupled from production. This has resulted in greater market orientation and a situation in which farmers face increased price variability. Policy now emphasises the development of business risk management (BRM) programmes, such as crop and whole farm insurance. However, for various reasons EU‐wide adoption of BRM programmes and farmer uptake and use of risk instruments is below expectations. We recommend the use of farm‐specific savings accounts upon which farmers can draw when revenues fall below a proportion of expected revenue. Farmer‐Directed Precautionary Savings Accounts (FDPSAs) would complement traditional non‐financial, on‐farm risk management strategies and private/public risk transfer strategies. FDPSAs would protect farmers against shallow losses and, along with crop and/or index‐based insurance, also protect against deep losses. Further, this form of protection is easy to understand and administer and leaves complete control with the producer. Abstract : Through a series of reforms, the European Union (EU) replaced most of its trade distorting price support programmes with safety net provisions and direct payments decoupled from production. This has resulted in greater market orientation and a situation in which farmers face increased price variability. Policy now emphasises the development of business risk management (BRM) programmes, such as crop and whole farm insurance. However, for various reasons EU‐wide adoption of BRM programmes and farmer uptake and use of risk instruments is below expectations. Abstract : À travers une série de réformes, l'Union européenne (UE) a remplacé la plupart de ses programmes de soutien des prix faussant les échanges par des mesures de filet de sécurité et des paiements directs découplés de la production. Cela a abouti à une plus grande orientation par le marché et à une situation dans laquelle les agriculteurs sont confrontés à une variabilité accrue des prix. La politique met désormais l'accent sur l'élaboration de programmes de gestion des risques de l'entreprise, tels que les assurances récolte et de l'exploitation dans son ensemble. Cependant, pour diverses raisons, l'adoption de ces programmes de gestion des risques dans l'ensemble de l'UE et l'adoption et l'utilisation par les agriculteurs d'instruments de gestion du risque sont en deçà des attentes. Nous recommandons l'utilisation de comptes d'épargne spécifiques à une exploitation dans lesquels les agriculteurs peuvent puiser lorsque leurs revenus sont inférieurs à une certaine part des revenus attendus. Les comptes d'épargne de précaution à destination des agriculteurs (FDPSA) compléteraient les stratégies non financières traditionnelles de gestion des risques sur l'exploitation et les stratégies de transfert des risques privés / publics. Les FDPSA protégeraient les agriculteurs contre les pertes superficielles et, avec une assurance récolte et / ou basée sur un indice, protègeraient également contre des pertes importantes. En outre, cette forme de protection est facile à comprendre et à mettre en œuvre et elle laisse un contrôle complet au producteur. Abstract : Die Europäische Union (EU) hat infolge mehrerer Reformen den Großteil ihrer handelsverzerrenden Preisstützungsprogramme durch die Bereitstellung von „Sicherheitsnetzen" und durch entkoppelte Direktzahlungen ersetzt. Dies führte zu einer stärkeren Marktorientierung und zu einer Situation, in der die Landwirte größeren Preisschwankungen ausgesetzt sind. Die Politik konzentriert sich nun auf die Entwicklung von Programmen für das unternehmerische Risikomanagement (Business Risk Management, BRM), wie z. B. Ernteversicherungen und gesamtbetriebliche Versicherungen. Aus verschiedenen Gründen liegt die EU‐weite Einführung von BRM‐Programmen und die Verbreitung und Verwendung von Risikomanagementinstrumenten jedoch unter den Erwartungen. Wir empfehlen daher den Einsatz von betriebsspezifischen Sparkonten, auf welche die Landwirte zurückgreifen können, wenn ihre Einkünfte unter einen bestimmten Anteil der erwarteten Einnahmen fallen. Die von den Landwirten geführten Vorsorge‐Sparkonten (Farmer‐Directed Precautionary Savings Accounts, FDPSAs) würden die traditionellen, nichtfinanziellen Risikomanagement‐Strategien auf Betriebsebene sowie private/öffentliche Risikotransferstrategien ergänzen. FDPSAswürden Landwirte vor geringeren Verlusten schützen und in Verbindung mit einer Ernte‐ und/oder indexbasierten Versicherung auch vor großen Verlusten. Darüber hinaus ist diese Form des Schutzes einfach zu verstehen und zu verwalten; sie überlässt außerdem dem Produzenten die gesamte Kontrolle.